Characterizing non-communicable disease trends in undocumented migrants over a period of 10 years in Italy - Gianfrancesco Fiorini; Matteo Franchi; Giacomo Pellegrini; Antonello Emilio Rigamonti; Alessandro Sartorio; Nicoletta Marazzi; Giovanni Corrao; Silvano Gabriele Cella (Scientific Reports, 2023)
Abstract Undocumented migrants represent a large part of the population in Countries of the European Union (EU) such as Italy. Their health burden is not fully understood and likely to be related mainly to chronic conditions. Information on their health needs and conditions may help to target public health interventions but is not found in national public health databases. We conducted a retrospective observational study of non-communicable disease (NCD) burden and management in undocumented migrants receiving medical care from Opera San Francesco, a non-governmental organization (NGO) in Milan, Italy. We analyzed the health records of 53,683 clients over a period of 10 years and collected data on demographics, diagnosis and pharmacological treatments prescribed. 17,292 (32.2%) of clients had one or more NCD diagnosis. The proportion of clients suffering from at least one NCD increased from 2011 to 2020. The risk of having an NCD was lower in men than women (RR = 0.88, 95% CI 0.86–0.89), increased with age (p for trend < 0.001) and changed with ethnicity. African and Asian migrants had a lower risk than Europeans of cardiovascular diseases (RR 0.62 CI 0.58–0.67, RR 0.85 CI 0.78–0.92 respectively) and mental health disorders (RR 0.66 CI 0.61–0.71, RR 0.60 CI 0.54–0.67 respectively), while the risk was higher in Latin American people (RR 1.07 CI 1.01–1.13, RR 1.18 CI 1.11–1.25). There was a higher risk of diabetes in those from Asia and Latin America (RR 1.68 CI 1.44–1.97, RR 1.39 CI 1.21–1.60). Overall, migrants from Latin America had the greatest risk of chronic disease and this was true for diabetes, cardiovascular diseases and mental health disorders. Undocumented migrants demonstrate a significantly different health burden of NCDs, which varies with ethnicity and background. Data from NGOs providing them with medical assistance should be included in structuring public health interventions aimed at the prevention and treatment of NCDs. This could help to better allocate resources and address their health needs.